The influence of slurry viscosity on hydrocyclone performance - Waters, Jason G (Centre for Minerals Research, 2015)
Many of the empirical hydrocyclone cut size models available consider the feed solids content to be an important variable in determining the efficiency and resultant classification. However, feed viscosity as a whole is admittedly a more accurate variable to consider as it can be affected by many factors, including solids content, particle size distribution, particle size, mineralogy, pulp chemistry, particle shape and carrier fluid temperature. Earlier theoretical models did try to incorporate slurry viscosity but were developed for very low solids content systems due to the difficulty in measuring slurry viscosity at higher concentrations. Current hydrocyclone models being applied in industry have difficulty in predicting rheological fluctuations at constant solids content, for example with an increase in feed clay content. Investigations, focussed on expanding the studies of previous researchers in this area, were conducted. Experiments involved the design and operation of two test rigs incorporating three hydrocyclone sizes (75,100, 165 mm), with two different ore types (platreef ore, copper ore) from a secondary stage operation used as the feed material. A change in relative viscosity was investigated by altering the viscosity of the carrier fluid (water) by the addition of sucrose, and modification of the slurry temperature. Hydrocyclone feed flow rate and solids content were also modified. A custom made on-line tube rheometer allowed viscosities of feed concentrations of up to 43% (by vol.) to be measured over a range of shear rates (200/s to 1500/s). The slurries under investigation were found to be settling in nature, and therefore a decision was made to exclude data below the critical settling velocity of the tube. Rheological characterisations revealed both ore types exhibited Bingham plastic behaviour. A concentration versus viscosity relationship was determined from the rheological data and the resultant viscosity values were then linked to hydrocyclone efficiency. The significant findings of this work included the following: * Increased pulp viscosity achieved by 1) sucrose addition and 2) decreased slurry temperatures resulted in a drop in hydrocyclone performance attributed to the combined effect on the partition curve parameters namely - an increased cut size (d50c), decreased water split to O/F (C) and reduced value of alpha. *Increased pulp viscosity achieved by 3) feed solids content had dissimilar effects on the partition curve parameters. An optimum viscosity point was reached for water split to O/F and alpha parameters, however cut size increased with increased pulp viscosity. * Rheological effects on the cut size parameter appeared more significant for the largest of the three cyclone body diameters used in the study. This can be attributed to the decreased tangential velocities inside the larger cyclone radius. The combined rheology and hydrocyclone data from this thesis will provide useful validation data for the new hydrocyclone models currently being developed as part of the P9 project. The models are to be incorporated in the JKSimMet simulation package and consider the effects of viscosity in their equations for cut-size and water split.